Pathways to Excellence: Analyzing the Accomplishment of Tarung Derajat Athletes in POMNAS XIX 2025 - Marshella Dwi Patrisia; Fajar Awang Irawan (Universitas Negeri Semarang, 2026)
Tarung derajat is an indigenous Indonesian martial art, with achievements that are inseparable from the process of continuous training, competition experience, and the personal journey of athletes throughout their careers. This study aims to analyze the achievements of Central Java's tarung derajat at the 2025 POMNAS XIX event through an auto-ethnographic approach, placing the subjective experiences of athletes as the main source. The research method used was qualitative autoethnography. Data was obtained from the athletes' experiences, documentation of their achievements, interviews with coaches, and analysis of supporting documents. The results of the study showed that Central Java's tarung derajat athletes won 8 medals, including 3 gold medals, 3 silver medals, and 2 bronze medals at the 2025 POMNAS XIX event. This study provides a deeper understanding of the dynamics of combat sports performance, not only in terms of competition results but also in terms of the training process and athletes' life experiences. Further research recommendations suggest combining an auto-ethnographic approach with quantitative analysis of physical performance in order to produce a comprehensive picture of combat sports performance and support the development of athlete training at the regional and national levels.